Tyrosine hydroxylase as a therapeutic target: insights from adrenergic nerve and TNBC cell interactions - Yichen Luo; Yanhong Han; Huilong Nie; Minghao Feng; Cuiting Wei; Xiuling Ma; Kefeng Li; Zhuangzhuang Zhang; Guangxue Wang; Wenjun Pan; Xueyang Li; Liutong Yi; et al. (Journal of Molecular Medicine, 2026)

Functional Validation of the Phase I–II–III Detoxification Pathway in Azumapecten farreri using Optimized RNA Interference Technology - Limin Lu; Guanchao Zheng; Yichen Lin; Chenfan Dong; Jixing Peng; Haiyan Wu; Zhijun Tan (Marine Biotechnology, 2026)

Estimating pollutant dispersion based on reconstructed mean flow field in a two-dimensional street canyon using two-step physics-informed neural networks - Yichen Wang; Bingchao Zhang; Chao Lin; Hideki Kikumoto (Building and Environment, 2026)

Amino Acid Metabolic Remodeling in Bivalves Under Environmental Stress: Roles, Mechanisms, and Implications for Bivalve Health—A Review - Yichen Lin; Wei Chen; Jixing Peng; Xinnan Zhao; Yan Di; Mengmeng Guo; Yanfang Zhao; Haiyan Wu; Guanchao Zheng; Qianqian Geng; Zhijun Tan (Fishes, 2026)
Climate change and increasing instability in coastal marine environments have intensified stressors such as elevated temperature, hypoxia, salinity variation, and pollutant exposure, posing major challenges to the survival, health, and culture performance of bivalves. As economically important aquaculture species and key components of coastal ecosystems, bivalves are highly sensitive to environmental fluctuations, making their metabolic responses highly relevant to both physiological adaptation and aquaculture sustainability. Increasing evidence indicates that metabolic remodeling is an important adaptive strategy supporting bivalve tolerance to environmental stress, with amino acid metabolic remodeling emerging as one of its most sensitive and functionally important components. This review summarizes the major response patterns, key pathways, and potential regulatory mechanisms of amino acid metabolism in bivalves under different stress conditions. Different environmental stressors induce distinct yet integrated shifts in amino acid metabolism, including enhanced catabolism, carbon–nitrogen redistribution, osmotic regulation, and antioxidant defense, thereby supporting energy homeostasis and physiological stress tolerance in bivalves. By highlighting amino acid metabolic remodeling as a central mechanism of bivalve adaptation to environmental stress, this review provides insights into adaptive responses, metabolite-based indicators for monitoring aquaculture environments and bivalve health, and management strategies for improving resilience in bivalve aquaculture.

From structural features to mouse acute intraperitoneal toxicity prediction: a triple computational toxicology approach for safety assessment of flavonoids - Yichen Yang; Na Zhang; Ting Ren; Lijiao Zhao; Rugang Zhong; Ning Lin; Guohui Sun (Molecular Diversity, 2026)

Structuring urban carbon metabolism through cross-sectoral and cross-media linkages: Evidence from a high-density city - Yu Lin; Jiahao Shi; Yichen Dong; Qingbin Song; Ni Sheng; Chen Chen; Zongguo Wen (Sustainable Cities and Society, 2026)

Experimental investigation of nonlinear hydrodynamic properties of the T-foil on a high-speed trimaran - Shijie Liu; Lincen Han; Hongyu Lin; Shaoqing Liu; Xi Chen; Yichen Jiang (Ocean Engineering, 2026)

Engineering a tetrahedral framework nucleic acid-based nanomedicine for precise intracellular delivery of rapamycin to rescue senescent bone mesenchymal stem cells - Shibo Liu; Qiheng Yang; Hanghang Liu; Ze He; Xuehan Tang; Yichen Yang; Yunfeng Lin; En Luo (Chemical Engineering Journal, 2026)

Possible inter-room aerosol-mediated COVID-19 transmission in a quarantine hotel: A case study - Merrill LIM; Junjing YANG; Sze Tat TAN; Man XIAO; Chun Ping GAO; Vernon LEE; Yee Leong TEOH; James CHAN; Lin CUI; Yichen DING; Joanna SHEN; Ruixin LI; et al. (Building and Environment, 2026)

NUFIP1-engineered exosomes modulate propofol-induced neurotoxicity in neonatal rats via the ERS apoptotic pathway - Pengyue Zhao; Yang Yan; Bin Lan; Xingpeng Yang; Yizhao Ma; Yichen Bao; Lin Qi; Xiaohui Du; Songyan Li; Wen Sun (Apoptosis, 2026)

Dynamic cross-sector and media assessment of urban phosphorus metabolism: underlying mechanisms, environmental implications, and driving forces - Yichen Dong; Yu Lin; Qingbin Song; Ni Sheng; Chen Chen; Zongguo Wen (Environment, Development and Sustainability, 2026)

Comprehensive quality evaluation and principal component analysis of Crassostrea gigas from North Yellow Sea, China: characterizing nutritional, flavor, and functional profiles - Shanqin Huo; Jixing Peng; Xinnan Zhao; Yichen Lin; Xudong Li; Zhijun Tan (Journal of Oceanology and Limnology, 2026)

6PPD-Q driven rare and abundant taxa functional partitioning shapes soil ecological response - Xinwei Shi; Weitao Liu; Ruiying Shi; Yichen Ge; Xiang Li; Chuan Yin; Jinzheng Liu; Yuexing Zhao; Dasong Lin; Yuebing Sun (Journal of Hazardous Materials, 2025)

Stabilization of nanoemulsions using cold-water fish gelatin and whey protein isolates/fibrils - Yichen Lin; Yrjö H. Roos; Maurice O'Sullivan; Song Miao (Food Hydrocolloids, 2025)

Nanoconfined enzymatic cascade strategy for highly efficient synthesis of D-allulose - Kan Zhan; Anni Bao; Suhai Zhang; Liang Chen; Yichen Wan; Keke Hou; Jian Hao; Lin Chaoping; Zhiyong Sun; Renchao Zheng; Yuguo Zheng (Chemical Engineering Journal, 2025)

Unraveling hiatuses in black shales: Mechanisms and implications from the Lower Silurian Longmaxi Formation, South China - Yichen Liu; Benzhong Xian; Qianran Wu; Zhiyong Lu; Haocheng Shi; Mingjin Wu; Zhiyun Yu; Lin Zhao; Junyang Geng; Haiying Chen (International Journal of Coal Geology, 2025)

Synthesis, characterization, and in vitro hypolipidemic mechanisms of sugar-SA triazole conjugates as potent pancreatic lipase inhibitors - Ruge Cao; Jingxin Li; Yue Sun; Yichen Li; Xiao-Lin Zhang; Han Ding; Xue-Wei Liu (Food Chemistry, 2025)

Highly flexible Janus fabric based on TPU spraying and laser processing for personal thermal-wet management - Zixuan Xu; Yulun Wu; Shuqiang Min; Lin Hu; Tonghuan Zhan; Heng Wang; Yan Yuan; Haojun Luo; Yichen Tang; Bing Xu (Chemical Engineering Journal, 2025)

Tribopotential mediated ferroelectric polarization for versatile reconfigurable p–n junction - Keteng Zhang; Jinran Yu; Yichen Wei; Liuqi Cheng; Zhenyu Feng; Jie Gong; Zhong Lin Wang; Qijun Sun (Chemical Engineering Journal, 2025)

High-frequency sequence patterns in lacustrine basins: Insights from delta-hyperpycnal flow systems in the Middle Jurassic shale interval, Sichuan Basin, China - Haocheng Shi; Benzhong Xian; Yichen Liu; Zhiyun Yu; Lin Zhao; Junyang Geng; Rongheng Tian; Qianran Wu; Li Liu; Yujie Shuai; Yi Shu (Sedimentary Geology, 2025)

Genetic Correlations and Causalities between Alzheimer’s Disease and 35 Biomarkers in Blood and Urine - Sheng Zhang; Yu-Lin Yao; Yichen Li; Xiaofan Zhang; Yong Wu (Molecular Neurobiology, 2025)

Enlarged Perivascular Spaces (EPVS) Associated with Functional and Cognitive Outcome After Aneurysm Subarachnoid Hemorrhage (aSAH) - Haichao Wang; Qiuyue Yu; Wenyi Zhang; Shengqi Yao; Yun Zhang; Qiong Dong; Yichen Zhao; Jinxing Lin; Xueyuan Liu; Li Gong (Translational Stroke Research, 2025)

Tetrahedral framework nucleic acid-based delivery of microRNA-29b: A precision nanotherapeutic strategy for oral submucous fibrosis - Xiao Fu; Mei Zhang; Chenpeng Chen; Xin Qin; Qianqian He; Yichen Yang; Siqi Xu; Guanjun Chen; Haiyu Xian; Guanyu Sun; Yao He; Yunfeng Lin; et al. (Chemical Engineering Journal, 2025)

Uplift, tilting, and underlying structures of coastal northwestern Luzon, Philippines, deduced from marine terraces - Yiran Wang; Aron J. Meltzner; Jennifer Quye-Sawyer; Huili Yang; Yichen Pu; Jintang Qin; Lin Thu Aung; Zihan Aw; Andrea Denise A. Pamintuan; Noelynna T. Ramos (Quaternary Science Reviews, 2025)

Dynamic variations in flavor profiles of Guizhou high-mountain white tea produced by Eurotium cristatum using solid-state fermentation - Su Xu; Linyao Song; Dajuan Shi; Siyao Wu; Fengwei Ma; Haijiang Chen; Qinglong Meng; Qiang Fei; Lingshuai Meng; Wenneng Wu; Dong Lin; Guangcan Tao; et al. (Food Bioscience, 2025)

Transglutaminase crosslinked fish gelatin emulsion gels: Structure, rheology behaviors, and delivery functionality - Yichen Lin; Yrjö H. Roos; Song Miao (Food Hydrocolloids, 2025)

Treatment of rheumatoid arthritis via tetrahedral framework nucleic acid‑based efficient delivery of Jakinib: Synergistic anti-inflammatory and osteogenic effects - Yichen Yang; Ruiqing Wang; Wumeng Yin; Ziqi Yue; Yuxuan Zhao; Zhou Jiang; Yunfeng Lin; Yao He; Shaojingya Gao; Xiaoxiao Cai (Chemical Engineering Journal, 2025)

Tight origin and hydrocarbon potential of shell interlayers in shale: A case of Lower Jurassic Dongyuemiao member, Sichuan Basin, China - Zhiyun Yu; Benzhong Xian; Zhenkui Jin; Qianran Wu; Yi Shu; Haocheng Shi; Junyang Geng; Lin Zhao; Yichen Liu (Marine and Petroleum Geology, 2025)

High-affinity uric acid clearance based on motile β-CD/F-127 polyrotaxane microspheres for enhanced diabetic wound repair - Xinlin Jiang; Zipeng Wu; Xiaoru Tan; Yichen Lin; Hui Xing; Yinglin Xuan; Dong Ma; Xin Cui (Carbohydrate Polymers, 2025)

Use of the diffusive gradients in thin-films (DGT) technique for smart rapid biomonitoring of trace metals in aquaculture systems - Runmei Wang; Jian Lu; Jun Wu; Yichen Lin; Feng Li; Cui Zhang; Jianhua Wang; Yingmin Zhou; Xiupeng Yue (Marine Environmental Research, 2025)

The effect of whey/soy protein fibril systems on the properties of fish gelatin stabilized emulsion gels - Yichen Lin; Yrjö H. Roos; Song Miao (Food Hydrocolloids, 2025)

A trackable mitochondria-targeting nanosystem for mitochondrial redox and mitophagy regulation in diabetic retinopathy management - Yangxue Yao; Xiaoyu Lei; Xun Li; Yichen Ge; Yun Wang; Xin Qin; Yang Gao; Geru Zhang; Yunfeng Lin; Shaojingya Gao; Xiaoxiao Cai (Chemical Engineering Journal, 2025)

Regenerated carboxymethyl cellulose beads for selective removal of low-density lipoprotein from whole blood - Yichen Tian; Yuele Kong; Xiaodi Liu; Lei Chen; Li Wang; Lin Zhou; Guodong Wang; Qiang Zhang (Carbohydrate Polymers, 2025)

PupaNet: A versatile and efficient silkworm pupae (Bombyx mori) identification tool for sericulture breeding based on near-infrared spectroscopy and deep transfer learning - Haibo He; Hua Huang; Shiping Zhu; Lunfu Shen; Zhimei Lv; Yongkang Luo; Yichen Wang; Yuhang Lin; Liang Gao; Benhua Xiong; Fangyin Dai; Tianfu Zhao (Computers and Electronics in Agriculture, 2024)

Spaceborne high-spectral-resolution lidar ACDL/DQ-1 measurements of the particulate backscatter coefficient in the global ocean - Yichen Yang; Yudi Zhou; Iwona S. Stachlewska; Yongxiang Hu; Xiaomei Lu; Weibiao Chen; Jiqiao Liu; Wenbo Sun; Suhui Yang; Yuting Tao; Lei Lin; Weige Lv; et al. (Remote Sensing of Environment, 2024)

Evaluating thermal sensation in outdoor environments - Different methods of coupling CFD and radiation modelling with a human body thermoregulation model - Dharmasastha K; Haobin Liang; Junwei Lin; Yongxin Xie; Yichen Yu; Jian-lei Niu (Building and Environment, 2024)

Dynamic response analysis of a fully coupled aerodynamic-hydrodynamic-mooring-anchor floating offshore wind turbine - Dongsheng Qiao; Yichen Zhou; Binbin Xu; Jianmin Qin; Guoqiang Tang; Lin Lu; Jinping Ou (Ocean Engineering, 2024)

Characterization and immune role of class B scavenger receptor member 1 in spotted sea bass (Lateolabrax maculatus) - Yichen Fu; Chao Zhao; Changhong Lin; Bo Zhang; Lulu Yan; Bo Zhang; Pengfei Wang; Lihua Qiu (Fish & Shellfish Immunology, 2024)

Suppression of pathological neovascularization by anti-Flt1 peptide functionalized DNA tetrahedron - Bicai Tang; Yuting Yang; Yong Li; Yutian He; Yichen Ge; Yangxue Yao; Wenjuan Ma; Yunfeng Lin (Chemical Engineering Journal, 2024)

Bone tissue engineering based on sustained release of MiR29c-modified framework nucleic acids from an injectable hydrogel - Jiafei Sun; Yang Gao; Yangxue Yao; Yong Li; Maogeng Feng; Long Bai; Xingyu Chen; Yichen Ge; Yunfeng Lin; Xiaoxiao Cai (Chemical Engineering Journal, 2024)

Corrigendum to “Characterization and functional properties of pH- and heated time-induced aggregates from red lentil protein” [Food Structure 37 (2023) 100342] - Han Du; Yichen Lin; Catherine Stanton; Davor Daniloski; Emanuele Zannini; R. Paul Ross; Song Miao (Food Structure, 2024)

Arsenic(III) sorption on organo-ferrihydrite coprecipitates: Insights from maize and rape straw-derived DOM - Aminu Darma; Yichen Liu; Xing Xia; Yihao Wang; Lin Jin; Jianjun Yang (Chemosphere, 2024)

Transglutaminase crosslinked fish gelatins for emulsion stabilization: From conventional to Pickering emulsions - Yichen Lin; Han Du; Yrjö Roos; Song Miao (Food Hydrocolloids, 2023)

Heterogeneous activation of permonosulfate by biochar supporting CuCoFe layered double hydroxide for rapid degradation of phenanthrene - Lin Wu; Tao Jin; Dan Li; Liping Wang; Yichen Sun (Journal of Environmental Chemical Engineering, 2023)

Binary complexes of whey protein fibers/isolates and fish gelatins for emulsion stabilization - Yichen Lin; Han Du; Yrjö Roos; Song Miao (Food Hydrocolloids, 2023)

The role of the core microorganisms in the microbial interactions in activated sludge - Huimin Lin; Yichen Zheng; Yuankai Yang; Fengyi Liu; Kuo Yang; Bing Zhang; Xianghua Wen (Environmental Research, 2023)

An integrative protocol for one-step PCR amplicon library construction and accurate demultiplexing of pooled sequencing data - Jiahao Ni; Jiao Pan; Yaohai Wang; Tianhao Chen; Xinshi Feng; Yichen Li; Tongtong Lin; Michael Lynch; Hongan Long; Weiyi Li (Marine Life Science & Technology, 2023)

Dual photoelectrodes activate oxygen evolution and oxygen reduction reactions enabling a high-performance Zn-air battery and an efficient solar energy storage - Jia You; Bingqing Zhang; Xianlong Wang; Haoran Zhang; Lanlan Huang; Lihua He; Nanxin Li; Yichen Chang; Shiwei Lin (Chemical Engineering Journal, 2023)

Characterization and functional properties of pH- and heated time-induced aggregates from red lentil protein - Han Du; Yichen Lin; Catherine Stanton; Davor Daniloski; Emanuele Zannini; R. Paul Ross; Song Miao (Food Structure, 2023)

Relationships between EEG and thermal comfort of elderly adults in outdoor open spaces - Xiaoyan Ma; Lin Song; Bo Hong; Yichen Li; Yang Li (Building and Environment, 2023)

Continental-scale spatial distribution, sources, and health risks of heavy metals in seafood: challenge for the water-food-energy nexus sustainability in coastal regions? - Jian Lu; Yichen Lin; Jun Wu; Cui Zhang (Environmental Science and Pollution Research, 2021)

Effects of ultrasound on functional properties, structure and glycation properties of proteins: a review - Derong Lin; Qiuting Zhang; Lijuan Xiao; Yichen Huang; Zhengfang Yang; Zhijun Wu; Zongcai Tu; Wen Qin; Hong Chen; Dingtao Wu; Qing Zhang; Suqing Li (Critical Reviews in Food Science and Nutrition, 2021)

A Causal Role of the Cerebellum in Auditory Feedback Control of Vocal Production - Danhua Peng; Qing Lin; Yichen Chang; Jeffery A. Jones; Guoqing Jia; Xi Chen; Peng Liu; Hanjun Liu (The Cerebellum, 2021)

Combining ability and genetic diversity under low-temperature conditions at germination stage of maize (Zea mays L.) - Jiayue Zhang; Yichen Li; Ziwen Zhang; Hong Di; Lin Zhang; Xuerui Wang; Zhenhua Wang; Yu Zhou (Euphytica, 2021)

Severe Nitrate Pollution and Health Risks of Coastal Aquifer Simultaneously Influenced by Saltwater Intrusion and Intensive Anthropogenic Activities - Jun Wu; Jian Lu; Xiaohu Wen; Zhenhua Zhang; Yichen Lin (Archives of Environmental Contamination and Toxicology, 2019)